Kalibrasi Mikrometer Sekrup Eksternal Dengan Mengacu Pada Standar JIS B 7502 - 1994 Di Laboratorium Pengukuran Teknik Mesin Universitas Riau - Arief, Dodi Sofyan; Kurnia, Andry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Activities to determine the truth value of the appointment of a conventional measuring instruments and measuring ingredients by comparing against a standard measure that traceable to a national standard for the unit of measure and internationally is the purpose of the calibration so that the existing external micrometer screw in Mechanical Engineering Laboratory Measurements can be seen Riau University how much difference deviation between the right price with the price indicated by an external micrometer screw. In the external calibration process micrometer screws there are six components , namelymeasurement uncertainty: Uncertainty measuring gauge block, standard uncertainty micrometer resolution , standard uncertainty able to re- reading of the micrometer , standarduncertainty the effect of temperature , standard uncertainty geometric correction , wringing standard uncertainty. As a result of analysis obtained values Value uncertainty of measuringdevices external I micrometer screw at a rate of 95% coverage factor of k = 2 is U95 = ± 5,8092 mm with a gauge factor correction tool = 0,00025 mm. The uncertainty of the value ofan external measuring instrument micrometer screw II at a rate of 95% coverage factor of k = 2 is U95 = ± 5,8092 mm by measuring factor correction tool = 0,00025 mm. The uncertaintyof the value of an external measuring instrument micrometer screw III equal to 95% coverage factor of k = 2 is U95 = ± 5,8092 mm and measuring instrument correction factor = 0,00975 mm.Keywords: Dimensional metrology , calibration , micrometer , uncertainty